The Effect of Abdominal Lifting on Pain and Duration of the First Stage of Labor - Elly Susilawati; Septi Indah Permata Sari; Yanti Yanti (Poltekkes Kemenkes Palembang, 2026)
A safe delivery does not necessarily mean it is pain-free, as pain is a natural part of the birthing process. Most women are aware that labor is almost always accompanied by pain, but not all are optimally prepared to deal with it. This study was conducted to determine the effect of abdominal lifting on labor pain and duration of the first stage of labor. It was conducted from March to April 2022 at PMB Dince Safrina, Pekanbaru City. The type of research used is pre-experimental with a One Group Pretest–Posttest Design approach. The number of samples involved in this research was 23 respondents at PMB Dince Safrina, Pekanbaru City. The average pretest labor pain was 6.35 and the posttest labor pain was 2.61 with an average difference of 3.74, which means that there was a decrease in the labor pain score before and after being givenabdominal lifting massage Abdominal lifting massage has an effect on reducing labor pain in mothers giving birth in the first stageAbdominal Lifting, Duration Of The first stage, Labor, Pain